Unilateral ureteric obstruction: Role of renin angiotensin system blockade on renal recovery: An experimental study - Anand Sinha; Minu Bajpai; Shashank Panda; Saumya Ranjan; Meher C Sharma (Wolters Kluwer Medknow Publications, 2012)
Aims: To study and compare the effects of angiotensin II antagonist (Losartan) and angiotensin converting enzyme (ACE) inhibitor (Enalapril) on renal recovery following reversal of iatrogenic unilateral upper ureteric obstruction. Materials and Methods: Unilateral upper ureteric obstruction was created in 96 adult Wistar rats that were reversed after predetermined intervals. Losartan and Enalapril were given to different subgroups of rats following relief of obstruction. Rats were sacrificed and kidneys were subjected to planimetric and histopathological analysis. Results: Dorsal lumbotomy approach provided a rapid and safe approach to kidneys in rats. The planimetric and histopathological changes were most severe in the group of rats in whom obstruction was not relieved before sacrifice. Addition of Enalapril and Losartan significantly hastened the reversal of renal changes following relief of obstruction as compared with the group in which no treatment was given following reversal of blockade. Conclusions: Renin angiotensin system (RAS) is the major pathway responsible for renal damage following outflow obstruction. However, this damage can be reversed with the use of drugs acting on the RAS.